'If things of sight such heavens be/What heavens are those we cannot see': Marvell and Protestant Saumur in the 1650s. Issue 1 (29th June 2018) - Pittion, Jean-Paul
Abstract : Andrew Marvell spent the year 1656 and most of 1657 in Saumur, a town in France on the river Loire, where he accompanied, as tutor, young William Dutton. This essay describes the conditions, material and social, in which the young British gentlemen found themselves during their stay in Saumur. It considers the impact that their stay in the town may have had on their religious practices and attitudes, drawing attention to the debates about religious aspects of the English Revolution which took place within the local reformed church. Further, the essay notes the role played by Marvell in drawing John Milton's attention to the disputations against Socinianism held under Josué de la Place, a leading theologian from the Protestant académie of Saumur. Finally, it suggests that Marvell's 'A Dialogue Between the Resolved Soul and Created Pleasure' may be a reflection on the experience of British students and their tutors during their stay in the town.